Prevalence, Association Relation, and Dynamic Evolution Analysis of Critical Values in Health Checkup in China: A Retrospective Study - Chen, Jingfeng; Wu, Zhuoqing; Liu, Yanan; Wang, Lin; Li, Tiantian; Dong, Yihan; Qin, Qian; Ding, Suying (Frontiers in Public Health, 2021)
Objective: The critical values in health checkup play a key role in preventing the chronic diseases and reflecting the population health status. The aim of this study was to analyze the prevalence, association relation, and dynamic evolution of critical values in health checkup at a large physical examination center in China. Methods: Herein, we chose 33639 samples of physical examiners from January 2017 to December 2019. After strict exclusion processes combined with the critical values in health checkup reporting data, 2400 participants with at least one critical value were included. We firstly defined critical value list in health checkup for laboratory test, imaging, cervical cancer screening and electrocardiogram, then analyzed the distribution and significance of critical values of 2400 participants from different views, the association relation of 325 participants with more than one critical value, and the dynamic evolution of 164 participants attending the physical examination in two years from 2017 to 2019. Results: A total of 2400 participants were included in the retrospective study. The critical value prevalence of Thyroid Ultrasound (1.69%), ECG (0.95%), Lung Computed Tomography and Chest X-Ray (0.83%), Tumor Marker Test (0.81%), Liver Function Test (0.74%) and Routine Urine Test (0.61%) from 33639 participants was over 0.6%. The critical value of Blood Glucose Test, Liver Function Test, Kidney Function Test, Blood Lipid Test, Routine Urine Test, and Head Computed Tomography were significantly increased in the male (P<0.05), whereas the results were the opposite for the Routine Blood Test and Thyroid Ultrasound (P<0.01). Association relation analysis identified 20 and 6 effective rules for the male and the female respectively, where the critical values of Routine Urine Test and Blood Glucose Test played the central roles. Further, dynamic evolution analysis extracted 10 and 6 effective transfer paths for the male and the female respectively, indicating a higher persistence for the identified critical values. Conclusions: In conclusions, this study provides a new perspective to explore the population health status using the critical value reporting data in physical examination center, which can assist to support health management decision-making at the population level and prevention and treatment at the individual level.